Analisis Implementasi Kebijakan Pajak Progresif Kendaraan Bermotor Pada Samsat Cinere Depok II Tahun 2018-2020 - Maharani Octari Putri; Jiwa Pribadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The purpose of this study is to analyze the Progressive Tax policy implementation motor vehicles on the One-stop Administration Service Office of Cinere Depok II. This research discusses three problems: the Progressive Tax policy implementation motor vehic les, the obstacle factors, and solutions to solve the obstacles. Descriptive qualitative method is used as the method of this research, and the data is collected by interview method to several parties. According to the result of the study, from 2018 to 2020, the policy implementation of Progressive Tax motor vehicles in the One-stop Administration Service Office of Cinere Depok II is considered not going well from some aspects, and, there are still some obstacles to handle. There will be a problem when a taxpayer does not report the vehicles they sell because they forget to block or protect the sold vehicles, or problems caused by the lack of awareness of the people in paying the Progressive Tax.